IMPACT OF LOAN TO DEPOSIT RATIO AND QUICK RATIO ON RETURN ON ASSETS WITH FIRM SIZE AS A MODERATING VARIABLE: A STUDY ON ASEAN BANKING SECTOR (2012-2020) - Sukirno, Sukirno; Rahayu, Mega (Yayasan Education and Social Center, 2025)
The study aims to determine the effect of Loan to Deposit Ratio (LDR) and Quick Ratio (QR) on Return On Assets (ROA) moderated by Firm Size and their impact on Price Earning Ratio (PER). The study uses companies in the banking subsector listed on the Southeast Asian Stock Exchange from 2012 to 2020 as the object. The data are secondary, collected from company annual reports. Samples were chosen purposively, obtaining 25 companies with complete financial reporting, resulting in 225 samples. Analysis methods include descriptive analysis, classical assumptions testing, moderated regression analysis (MRA), multiple linear regression, partial testing (t-test), and simultaneous testing (F-test). Results show that LDR has a significant effect on ROA; QR has no significant effect on ROA; together LDR and QR significantly affect ROA simultaneously. Firm Size does not moderate the relationship between LDR and ROA, nor between QR and ROA. ROA has no significant effect on PER.